2014
DOI: 10.1590/s1413-41522014019000000468
|View full text |Cite
|
Sign up to set email alerts
|

O Conselho Municipal de Saneamento de Belo Horizonte: desafios e possibilidades

Abstract: The Municipal Council of Sanitation (COMUSA) of Belo Horizonte (MG, Brazil) was created in April, 2004. Since it is recently founded, mainly when compared to other existent municipal councils in Belo Horizonte (environmental and health, among others), COMUSA was conceived with expectations of a good operation, since it could be guided by the previous experience of the oldest councils.However, the Council still has some fragility, mainly structural, which brings barriers to its operation. This study aims to eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 5 publications
1
4
0
5
Order By: Relevance
“…Thus, it became impossible to analyze this council regarding this variable. This undermines the proposed study but reinforces the analysis made in another study 23 , which also highlighted this limitation of the referred council. It also suggests the possibility that the minutes are being taken as a mere obligation to be met in compliance with legal requirements 10 .…”
Section: Dynamics Of the Deliberative Procedures In The Councilssupporting
confidence: 55%
See 2 more Smart Citations
“…Thus, it became impossible to analyze this council regarding this variable. This undermines the proposed study but reinforces the analysis made in another study 23 , which also highlighted this limitation of the referred council. It also suggests the possibility that the minutes are being taken as a mere obligation to be met in compliance with legal requirements 10 .…”
Section: Dynamics Of the Deliberative Procedures In The Councilssupporting
confidence: 55%
“…A single study was found on COMUSA 23 , and its conclusion highlights that, although with merits (brought and may bring even more positive changes to the sanitation scenario in Belo Horizonte), between 2004 and 2008, the council could not guarantee social control. There were limitations on the generation of own proposals and action on public policy, and there was a feeling that the approved definitions were just "done deal" proposals that the Municipality of Belo Horizonte (PBH) would carry out even if the council did not exist.…”
Section: Contextualization Of Councils Under Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The first of the aforementioned models corresponds to a tendency that was identified in Brazil during the military regime and, to a great extent, even afterwards 21 because there are still examples of the strong influence of this model limiting the participation of service users 7,22,23 . This is also currently the situation in Mexico, among other countries 24 .…”
Section: Social Control In Sanitation and In Healthmentioning
confidence: 98%
“…Além disso, a relevância do trabalho também se evidencia pela contribuição que poderá dele advir para a área de saneamento básico e saúde ambiental, por três razões: (1) o saneamento tem ampla interface com a gestão hídrica, considerando-se, por exemplo, a captação de água para tratamento e distribuição para o abastecimento público e o lançamento de esgotos em corpos hídricos receptores, o que afeta a saúde pública e ambiental, requerendo uma visão estratégica participativa e intersetorial; (2) data apenas de 2007 a instituição legal de instrumentos participativos na área, o que representa ainda uma novidade para gestores e usuários, que poderão se beneficiar da experiência da gestão das águas; (3) têm sido identificadas dificuldades para colocar em prática os instrumentos legais participativos (Mello;Rezende, 2014;Piterman;Heller;Rezende, 2013). Na seção seguinte, são apresentadas breves considerações conceituais sobre controle social e, na sequência, estão a metodologia empregada para o alcance do objetivo proposto, os resultados obtidos e sua discussão e as considerações finais.…”
Section: Introductionunclassified